1996
DOI: 10.1021/ac9600619
|View full text |Cite
|
Sign up to set email alerts
|

DNA Biosensor for the Detection of Hydrazines

Abstract: A double-stranded (ds) DNA-coated carbon paste electrode is employed as a remarkably sensitive biosensor for the detection of hydrazine compounds. The sensor relies on monitoring changes in the intrinsic anodic response of the surface-confined DNA resulting from its interaction with hydrazine compounds and requires no label or indicator. Short reaction times (1-10 min) are sufficient for monitoring part-per-billion levels of different hydrazines. Applicability to untreated natural water samples is illustrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(76 citation statements)
references
References 13 publications
0
74
0
2
Order By: Relevance
“…17,[87][88][89][90][91][92] Changes in the DNA redox properties were reported for studies of interaction between DNA and analyte. 88,89,91 Moreover, the amount of electro-active substrate trapped on the DNA layer was investigated.…”
Section: ·11 Dna Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…17,[87][88][89][90][91][92] Changes in the DNA redox properties were reported for studies of interaction between DNA and analyte. 88,89,91 Moreover, the amount of electro-active substrate trapped on the DNA layer was investigated.…”
Section: ·11 Dna Biosensorsmentioning
confidence: 99%
“…17,[87][88][89][90][91][92] Changes in the DNA redox properties were reported for studies of interaction between DNA and analyte. 88,89,91 Moreover, the amount of electro-active substrate trapped on the DNA layer was investigated. 87 Thus, it was concluded that electrochemical biosensors offered an easier immobilization of the DNA layer and faster measurement Flow injection analysis with an evanescent wave biosensor was coupled for the detection of DNA intercalator on the basis of their different affinities for double-stranded DNA at a constant concentration of the ethidium bromide.…”
Section: ·11 Dna Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diversos são os materiais de eletrodo que podem ser modificados com DNA, vale dizer, mercúrio 8,[91][92][93][94][95] , ouro [96][97][98][99][100][101] , grafite 95,102 , pasta de carbono 89,[103][104][105][106][107][108][109][110][111][112][113][114][115] e carbono vítreo 47,80,100,[116][117][118][119][120][121][122][123] . Muitos destes exemplos já estão sendo, genericamente, denominados biossensores eletroquímicos de DNA ou genossensores 78 .…”
Section: Eletrodos Modificados Com Dnaunclassified